M Way Mahathir's economic legacy - Jomo K. S (Jomo Kwame Sundaram) (Forum, 2003)
This introduction to the book M Way reviews Mahathir's economic policy legacy from the early 1980s especially his major innovations in development policy, including the Look East policy, the 70 million population policy, the National Agriculture Policy, heavy industrialization, 'Malaysia Incorporated', privatization and the 1998 national economic recovery strategy involving capital and currency controls. It also examines the way in which Mahathir dealt with the New Economic Policy and subsequently introduced successor policies such as Vision 2020 as well as the National Development Policy and the National Vision Policy